2018
DOI: 10.1148/rg.2018170079
|View full text |Cite
|
Sign up to set email alerts
|

Liver Iron Quantification with MR Imaging: A Primer for Radiologists

Abstract: Iron overload is a systemic disorder and is either primary (genetic) or secondary (exogenous iron administration). Primary iron overload is most commonly associated with hereditary hemochromatosis and secondary iron overload with ineffective erythropoiesis (predominantly caused by β-thalassemia major and sickle cell disease) that requires long-term transfusion therapy, leading to transfusional hemosiderosis. Iron overload may lead to liver cirrhosis and hepatocellular carcinoma, in addition to cardiac and endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
137
1
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 141 publications
(142 citation statements)
references
References 77 publications
(140 reference statements)
0
137
1
4
Order By: Relevance
“…Estimates of PDFF were similar between field strengths, but R2* values were generally higher at 3T. The mean liver R2* value was 37.2 ± 6.8 s −1 at 1.5T and 59.8 ± 12.9 s −1 at 3T, and R2* values were generally in the normal range (<60 s −1 at 1.5T, <126 at 3T) . The distributions of baseline PDFF and R2* values are summarized in Fig.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…Estimates of PDFF were similar between field strengths, but R2* values were generally higher at 3T. The mean liver R2* value was 37.2 ± 6.8 s −1 at 1.5T and 59.8 ± 12.9 s −1 at 3T, and R2* values were generally in the normal range (<60 s −1 at 1.5T, <126 at 3T) . The distributions of baseline PDFF and R2* values are summarized in Fig.…”
Section: Resultsmentioning
confidence: 75%
“…One of the reasons this study is clinically relevant is that in patients with NAFLD, liver iron deposition may portend worse clinical outcomes . Since MRI‐based measures such as R2* estimation have all but replaced liver biopsy for assessment of liver iron concentration in other populations, investigators logically may attempt to use measurements of R2* to quantify liver iron in patients with NAFLD . However, our data show that hepatic steatosis, as quantified by PDFF, substantially confounds R2* measurements in this population.…”
Section: Discussionmentioning
confidence: 88%
“…Our goal was to remain consistent with the original methodology described by Wood et al Finally, our sample only included participants with transfusional hemosiderosis. Patients with hemochromatosis, a nontransfusional hemosiderosis, exhibit a different LIC distribution compared with conditions such as beta‐thalassemia and sickle cell disease …”
Section: Discussionmentioning
confidence: 99%
“…The first large study validating R2* relaxometry showed that the R2* calibration curve with liver biopsy was linear . R2* has many advantages over other MRI iron quantification techniques, such as fast acquisition time, wider detection range of liver iron content, and more robust results for tracking chelation response after short treatment periods . However, R2* relaxometry's capacity to calculate liver iron concentration (LIC) is limited in patients with severe iron overload .…”
mentioning
confidence: 99%
See 1 more Smart Citation